(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
ABSTRACT: This article addresses the issue of racial (in)equality in the judiciary. Therefore, a brief report on the subject from its origins to the remains found today is presented, as well as the main judicial policies on racial equality implemented within the scope of the Judiciary, especially those applied through the Ordinance No. 108 of 7/8/2020 of the National Council of Justice, which creates the Working Group for the preparation of studies and indication of solutions with a view to formulating judicial policies on racial equality within the scope of the Judiciary. It also discusses the concepts of racism, and structural racism, in order to clarify the ways in which discrimination can occur. KEYWORDS: Institutional racism. Principle of equality. Judicial power.